Is obesity a contributing factor to female infertility? - a literature review - Frank, Marta; Falkowski, Dawid; Kozłowska, Magdalena; Kozłowski, Gracjan; Łabuda, Julia; Rewaj-Nowicka, Urszula; Szwedo, Jowita (Quality in Sport, 2025)
Introduction and purpose: Obesity has emerged as one of the most pressing public health issues worldwide, with significant implications for female reproductive health. This review examines the complex relationship between obesity and infertility, emphasizing how obesity disrupts hormonal balance, metabolic processes, and ovarian function, leading to infertility. Material and methods: Medical databases like PubMed and Google Scholar were searched for scientific papers on impact of obesity on female infertility. These were analyzed and summarized in this review. State of knowledge: The hormonal imbalances associated with obesity, such as insulin resistance and elevated androgen levels, are closely linked to ovulation disorders, particularly in conditions like polycystic ovarian syndrome (PCOS). Furthermore, obesity negatively impacts oocyte quality, endometrial receptivity, and the success of assisted reproductive technologies (ART), such as in vitro fertilization (IVF). The review also explores potential interventions, including lifestyle modifications, pharmacological treatments, and bariatric surgery, to improve fertility outcomes in obese women. Conclusion: Addressing obesity is crucial in managing female infertility, and an integrative approach combining prevention, treatment, and ART advancements is essential for improving reproductive health. This work underscores the need for continued research and multidisciplinary collaboration to optimize fertility outcomes for obese women.